Determination of Flavonoid Content of Ethanol Extract of Leaves and Bark of Ebony (Diospyros celebica Bakh) Using UV-Vis Spectrophotometry Method - Hasju, Hasriyati (Makassar Natural Product Journal (MNPJ), 2024)
Ebony (Diospyros celebica Bakh) is a plant belonging to the Ebenaceae family which is one of the endemic plants from Sulawesi, Indonesia. Previous research has proven that ebony leaves are used as a traditional medicine to lower blood sugar levels, while the bark of ebony stems can be used as an antibacterial. Ebony leaves and bark contain secondary metabolites, namely flavonoids, alkaloids, terpenoids, steroids, tannins and saponins. This study aims to determine and determine the levels of flavonoids contained in extracts of leaves and bark of ebony stems. Flavonoid compounds have antioxidant, antibacterial, hypoallergenic, antiviral, anticancer and antidiabetic activities. The research method used to obtain the extract was the soxhletation method with 96% ethanol. The method used in the determination of flavonoid levels is using UV-Vis spectrophotometry with quercetin as a reference standard. Quercetin is a class of flavonoids belonging to the flavonol. Test results on UV-Vis Spectrophotometry with a wavelength of 430 nm, obtained flavonoid levels from ebony leaf samples, namely 7.999 mgQE/g extract, and in ebony bark, flavonoid levels obtained were 6.087 mgQE/g extract.